When Paul's Desire and God's Will Collide: A Reading of Romans 9:1–18 - Kozman, Rony (My University, 2013)
This thesis proposes a new reading of Romans 9:1–18. The history of biblical interpretation of the passage is explored with the purpose of mapping out the diversity of interpretations and noting points of agreement between these interpretations and that which is proposed. The main objective is the proposed reading of Rom 9:1–18. It is argued that when full weight is given to Rom 9:1–5 as Paul's fleshly desire, what follows in 9:6–18 is correctly understood as Paul's appropriation of Israel's Scripture to address his own desire and grief. This brings to the fore a recurrent theme in the pentateuchal passages that Paul evokes: the conflicting desire of significant figures in Israel's history – Abraham, Isaac, and Moses – with God's will. As Paul applies Scripture to his own situation, Paul's desire for the salvation of his fellow Israelites based on ethnic descent conflicts with God's will to harden Israel and call Gentiles. But in the end Paul's desire for Israel's salvation is granted (11:26).
Keywords: Romans; Paul; Scripture; Intertextuality; Biblical Studies; Biblical Studies